2000
DOI: 10.1002/(sici)1097-010x(20000301)286:4<379::aid-jez6>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic muscle development in rainbow trout (Oncorhynchus mykiss): A scanning electron microscopy and immunohistological study

Abstract: Embryonic muscle development was studied in rainbow trout (Oncorhynchus mykiss) at low and high temperature using scanning electron microscopy (SEM) and immunohistology. Somite development was described starting at stage 16 (Vernier JM. 1969. Ann Embryol Morphogen 4:495–520) for both temperatures, with special interest in their shape and size. Muscle differentiation, associated with somite growth, is characterized by a larger increase in height compared to width and by acquisition of a chevron shape. Thin stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…The rate of somitogenesis observed here (5.7 somites formed/day at 8 °C, i.e. 0.7 somite formed/degree-day) is consistent with previous observations in the same species (Bobe et al, 2000). Other data with rainbow trout have indicated that the initial differentiation of fast (white) muscle takes place in proximity to axial structures and that fmhc transcript is detected from 25 somites onwards (Rescan et al, 2001).…”
Section: Embryonic Myogenesis and Arg Or L-name Bathssupporting
confidence: 93%
“…The rate of somitogenesis observed here (5.7 somites formed/day at 8 °C, i.e. 0.7 somite formed/degree-day) is consistent with previous observations in the same species (Bobe et al, 2000). Other data with rainbow trout have indicated that the initial differentiation of fast (white) muscle takes place in proximity to axial structures and that fmhc transcript is detected from 25 somites onwards (Rescan et al, 2001).…”
Section: Embryonic Myogenesis and Arg Or L-name Bathssupporting
confidence: 93%
“…Embryonic genome activation occurs at mid-blastula stage in fish. According to Bobe and coworkers (2000), mid-blastula stage of rainbow trout embryos (cultured at ~12°C) occurs 2-dpf [35,36]. So, maternal mRNA degradation and EGA in rainbow trout could occur around 2-dpf.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative studies on myogenesis showed that in vertebrates the process does not follow a common developmental pathway, and the ways leading to formation of multinucleate muscle fibres in early embryogenesis are different in fishes, amphibians, birds and mammals (reviewed by Kiełbówna and Daczewska, 2004). In fishes, at early stages of myogenesis, primary myoblasts (of mesodermal origin) differentiate into multinucleate muscle lamellae in Siberian sturgeon ( Acipenser baeri ) and starry sturgeon ( Acipenser stellatus ) (Flood and Gulyaev, 1987; Daczewska and Saczko, 2005) or form multinucleate myotubes in European grayling ( Thymallus thymallus ), rainbow trout ( Oncorhynchus mykiss ), European pearlfish ( Rutilus frisii meidingeri ) and Atlantic salmon ( Salmo salar ) (Merkel, 1995; Stoiber et al., 1998; Johnston, 1999; Bobe et al., 2000). In amphibians myotomal cells were observed to differentiate into mononucleate, morphologically and functionally mature muscle cells in African clawed frog ( Xenopus laevis ), and African dwarf frog ( Hymenochirus boettgeri ) (Daczewska, 2001; Kiełbówna and Daczewska, 2005), or else multinucleate myotubes form directly in European spadefoot ( Pelobates fuscus ), pool frog ( Rana laessonae ), and smooth newt ( Triturus vulgaris ) (Daczewska and Pałucka, 1999; Daczewska and Kiełbówna, 2000).…”
Section: Introductionmentioning
confidence: 99%